2022
DOI: 10.1136/bmjopen-2021-057885
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological therapies for postviral syndromes, including Long COVID: a systematic review and meta-analysis protocol

Abstract: IntroductionPostviral syndromes (PVS) describe the sustained presence of symptoms following an acute viral infection, for months or even years. Exposure to the SARS-CoV-2 virus and subsequent development of COVID-19 has shown to have similar effects with individuals continuing to exhibit symptoms for greater than 12 weeks. The sustained presence of symptoms is variably referred to as ‘post COVID-19 syndrome’, ‘post-COVID condition’ or more commonly ‘Long COVID’. Knowledge of the long-term health impacts and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…In the meantime, some researchers have offered reviews of the post-viral syndrome literature to guide intervention development. For example, Chandan [ 11 ] found that pilates, telerehabilitation, resistance exercise, and neuromodulation showed some support in symptom management. In the few published intervention studies with Long-COVID patients, physical rehabilitation has been a focus.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, some researchers have offered reviews of the post-viral syndrome literature to guide intervention development. For example, Chandan [ 11 ] found that pilates, telerehabilitation, resistance exercise, and neuromodulation showed some support in symptom management. In the few published intervention studies with Long-COVID patients, physical rehabilitation has been a focus.…”
Section: Introductionmentioning
confidence: 99%
“…The study was not adequately powered; therefore, further work may be necessary to assess efficacy (Chandan et al, 2022).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Two SRs indicated that non-pharmaceutical interventions for patients with Long COVID or CFS could help improve function for activities of daily life (Fowler-Davis et al, 2021; Larun et al, 2019). However, the third and most recent SR concluded that there is a lack of robust evidence for non-pharmaceutical interventions (Chandan et al, 2022).…”
Section: Rapid Review Detailsmentioning
confidence: 99%
See 2 more Smart Citations